The Role of Automated Processing in Teaching the Grammatical Rules of the Arabic Language - A Study on the Arabic Writing System - Bourafa, Hassiba; Chibani, Abd alouaheb (Milev Journal of Research and Studies, 2021)
This study seeks to attempt to shed light on how to process and engineer the texts and grammar of the Arabic language on the computer, and encode them using a set of technologies and software present in the digital content. As the Arabic language is a natural, mathematical and etymological language par excellence, this research aims in the end to obtain an automated educational method to make it easier for every learner to acquire Arabic linguistic structures through modern scientific schemes. Therefore, we chose the topic: "The role of automated processing in teaching the grammatical rules of the Arabic language - a study on the Arabic writing system - trying to answer the following forms: What are the mechanisms and mechanisms that depend on it in processing Arabic grammar automatically? We follow the descriptive-analytical approach. The research aimed to achieve a set of results, the most important of which is: The Arabic language is a mathematical language par excellence, whose rules can be reduced and shortened and programmed in the computer to facilitate the method of its acquisition.